2018
DOI: 10.1002/chem.201804865
|View full text |Cite
|
Sign up to set email alerts
|

Newly Synthesized Lipid–Porphyrin Conjugates: Evaluation of Their Self‐Assembling Properties, Their Miscibility with Phospholipids and Their Photodynamic Activity In Vitro

Abstract: Lipid–porphyrin conjugates are considered nowadays as promising building blocks for the conception of supramolecular structures with multifunctional properties, required for efficient cancer therapy by photodynamic therapy (PDT). The synthesis of two new lipid–porphyrin conjugates coupling pheophorbide‐a (Pheo‐a), a photosensitizer derived from chlorophyll‐a, to either chemically modified lyso‐phosphatidylcholine (PhLPC) or egg lyso‐sphingomyelin (PhLSM) is reported. The impact of the lipid backbone of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 74 publications
5
31
0
Order By: Relevance
“…Conjugation dose not significantly change the electron absorption and photosensitivity of PS. For instance, as building blocks, conjugates of lipid‐porphyrin ( PpIX‐Ole , [ 95 ] PL‐C17 , [ 96 ] PhLPC , PhLSM , [ 97 ] and PC‐BPD [ 61 ] ), AIEgen‐lipid , [ 93 ] and lipid‐ICG ( iDOPE [ 89 ] and ICG‐C18 [ 98 ] ) were incorporated into liposomes by self‐assembly (Figure 5 ). Free PS and lipid‐PS conjugates encapsulated in liposomes induce cell death via different pathways.…”
Section: Construction Of Liposomal Systems For Pdtmentioning
confidence: 99%
“…Conjugation dose not significantly change the electron absorption and photosensitivity of PS. For instance, as building blocks, conjugates of lipid‐porphyrin ( PpIX‐Ole , [ 95 ] PL‐C17 , [ 96 ] PhLPC , PhLSM , [ 97 ] and PC‐BPD [ 61 ] ), AIEgen‐lipid , [ 93 ] and lipid‐ICG ( iDOPE [ 89 ] and ICG‐C18 [ 98 ] ) were incorporated into liposomes by self‐assembly (Figure 5 ). Free PS and lipid‐PS conjugates encapsulated in liposomes induce cell death via different pathways.…”
Section: Construction Of Liposomal Systems For Pdtmentioning
confidence: 99%
“…Lipid-porphyrin conjugates are considered, nowadays, as promising building blocks for the conception of supramolecular structures with multifunctional properties, required for efficient cancer treatment by photodynamic therapy. Two lipid-porphyrin conjugates synthesized by coupling pheophorbide-a (Pheo-a), a photosensitizer derived from chlorophyll-a, to either chemically modified lyso-phosphatidylcholine (PhLPC) or egg lyso-sphingomyelin (PhLSM) were investigated to understand the impact of the lipid backbone of these conjugates on their self-assembly, as well as their physicochemical properties, including interfacial behavior at the air-buffer interface, fluorescence and absorption properties, thermotropic behavior, and incorporation rate in the membrane of liposomes [171]. XRR demonstrated that both lipid-porphyrin conjugates could be efficiently incorporated into lipid vesicles, with higher loading rates than unconjugated Pheo-a, as illustrated in Figure 19.…”
Section: Model Biological Membranesmentioning
confidence: 99%
“…Porphyrins and metalloporphyrins have attracted increasing attention because of their potential applications in photodynamic therapy, solar energy conversion, biomimetic catalysis and so forth . Therefore, innovation and improvement in the synthesis of porphyrins are crucially important in porphyrin chemistry .…”
Section: Introductionmentioning
confidence: 99%